Development of a Simple Risk Model to Predict Mortality in Patients With Osteosarcoma of the Extremity - Chen, Yu; Li, Chao; Wang, Xin; Liu, Zhiyong; Ren, Zhigang (Frontiers in Medicine, 2022)
Background Osteosarcoma (OS) is the most prevalent primary malignant bone sarcoma affecting mainly children and the outcome is poor in patients with metastatic disease at present or in relapse. Therefore, the aim of this study was to explore the clinical data of patients with osteosarcoma of the extremity at primary diagnosis, determine the prognostic factors that influence survival, and build up and validate a simple risk model to predict mortality in OS patients. Materials and Methods This was a single center retrospective cohort study.153 patients with newly diagnosed OS were enrolled as training group. We analyzed the clinical data and outcomes of the OS patients. Prognostic risk factors were identified by a logistic regression model with Markov Chain Monte Carlo (MCMC）simulation, Risk score was constructed based on the training group and was further validated using each patients. Results The total of the 153 patients, the mean (SD) age was 21.6 (14.2) years, 62(40.5%) patients were females. The rate of in-hospital mortality of patients was 41.2% (95%CI, 31.6%-50.7%). The candidate prognostic factors were selected and evaluated in relation to patient age, gender, tumor site (lower/upper extremity), tumor volume, intramedullary length of lesion, serum levels of alkaline phosphatase (ALP) and primary metastasis. However, only tumor size and primary metastasis were identified as independent prognosis indicators for patients with osteosarcoma. The risk model had C-statistic was 0.7308 with a predictive range of 21.05%-68.42%. Based on distribution of the risk score, 24.8%, 49.7% and 25.5% of patients were stratified to the high, average and low-risk groups for in-hospital mortality, with corresponding probabilities of 0.684, 0.329, and 0.210, respectively. Conclusion A simple risk model was developed and validated to predict the prognosis for patients with osteosarcoma of the extremity at primary diagnosis. The simple risk score system might be used to stratify patients into different risk groups of in-hospital mortality and may help to clinicians to judge the outcomes of prognosis and establish appropriate surveillance strategies.